Oficina C: Towards a Collective Intelligence to Meet the Challenges of Parliamentary Work in Spain (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
The integration of scientific knowledge into parliamentary work is increasingly recognised as a cornerstone of democratic resilience in the twenty-first century. Confronted with global challenges such as climate change, digital transformation, demographic ageing, and political polarisation, parliaments must enhance their ability to deliberate on complex and uncertain issues. In Spain, the creation of Oficina C, the Science and Technology Office of the Congress of Deputies, represents a decisive step towards institutionalising science advice for democratic governance and strengthening trust between citizens and political institutions.